1996
DOI: 10.1093/ajcn/64.3.472s
|View full text |Cite
|
Sign up to set email alerts
|

Clinical detection of sarcopenic obesity by bioelectrical impedance analysis

Abstract: To assess whether bioelectrical impedance analysis (BIA) provides clinically useful information on body composition beyond that obtained from measuring height and weight, we clinically classified 306 obese patients (233 females and 73 males) into tertiles of increasing fat-free mass estimated by BIA. Because fat-free mass by BIA is an estimate of lean body mass, the lowest tertile was clinically defined as sarcopenic obesity (reduced lean body mass), as contrasted with proportionate or muscular obesity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 6 publications
0
85
0
8
Order By: Relevance
“…Initial studies proposed the clinical detection of sarcopenic obesity by bioelectrical impedance analysis (27) but later reports emphasized the importance of using more sophisticated measurements such as DXA through clinical examination (22). Although Newman et al (4) had considered FM and height in their approach, they did not use the term sarcopenic obesity in their report.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies proposed the clinical detection of sarcopenic obesity by bioelectrical impedance analysis (27) but later reports emphasized the importance of using more sophisticated measurements such as DXA through clinical examination (22). Although Newman et al (4) had considered FM and height in their approach, they did not use the term sarcopenic obesity in their report.…”
Section: Discussionmentioning
confidence: 99%
“…The major shortcoming of the body mass indices is that the actual composition of the body is not taken into account: the excess body mass may be made up of fat mass or fat-free mass, both of which will be judged as excess mass. On the other hand, a deficit of the body mass may be due to a fat-free mass deficit or mobilization of fat mass, or both combined (Heber et al, 1996). In terms of body composition, it has been observed that, in each sex, annual increases in BMI were driven primarily by increases in fat free mass/ stature 2 until late adolescence, with increases in total body fat/stature 2 contributing to a larger proportion of the BMI increases in girls than in boys (Maynard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coef®cient between BMI values and body mass percentage by DXA method was only 0.605, compared to BIA, which was 0.889. Even though the calculation of body fat mass percentage was done from the BMI (by the formula by Garrow and Webster; Heber et al, 1996), the correlation coef®cient was only slightly improved to 0.625.…”
Section: Underestimation Of Body Fat Mass J Eisenko èLbl Et Almentioning
confidence: 99%